Permanence of youth in rural environment: beyond traditional generational succession - Spanevello, Rosani Marisa (2021)
A permanence of young people in the rural areas has been presented in a different way from the traditional model of generational succession. This article aims to assess the ways in which young people remain in rural areas today, with emphasis on the differences regarding the traditional generational succession process. 53 interviews were analyzed in different municipalities in the northwest region of Rio Grande do Sul. The analysis of the results pointed to four different forms of permanence: 1) Residence together (same house) on the paternal property with agricultural and non-agricultural activities; 2) Separate residence (but on the same property as the parents) with agricultural activities on the paternal properties; 3) Residence in the urban environment, with agricultural activities on the parents' properties and 4) Residence on the property, together with the parents and with urban activities. These four forms of permanence found in the results suggest that the traditional generational succession has given way to other arrangements with ramifications that include residing in rural or urban areas, having activities related to agriculture and livestock or mixing with non-agricultural activities, having autonomy in the family business and income.